Transposable element accumulation drives size differences among polymorphic Y Chromosomes in Drosophila - Nguyen, Alison H.; Wang, Weixiang; Chong, Emily; Chatla, Kamalakar; Bachtrog, Doris (Genome Research, 2022)
Y Chromosomes of many species are gene poor and show low levels of nucleotide variation, yet they often display high amounts of structural diversity. Dobzhansky cataloged several morphologically distinct Y Chromosomes in Drosophila pseudoobscura that differ in size and shape, but the molecular causes of their large size differences are unclear. Here we use cytogenetics and long-read sequencing to study the sequence content of polymorphic Y Chromosomes in D. pseudoobscura. We show that Y Chromosomes differ almost twofold in size, ranging from 30 to 60 Mb. Most of this size difference is caused by a handful of active transposable elements (TEs) that have recently expanded on the largest Y Chromosome, with different elements being responsible for Y expansion on differently sized D. pseudoobscura Y's. We show that Y Chromosomes differ in their heterochromatin enrichment and expression of Y-enriched TEs, and also influence expression of dozens of autosomal and X-linked genes. The same helitron element that showed the most drastic amplification on the largest Y in D. pseudoobscura independently amplified on a polymorphic large Y Chromosome in Drosophila affinis, suggesting that some TEs are inherently more prone to become deregulated on Y Chromosomes.